The impact of entrepreneurial passion on the entrepreneurial intention: Moderating impact of perception of university support - Temoor Anjum; Petra Heidler; Azadeh Amoozegar; Rao Tahir Anees (Administrative Sciences, 2021)
Passion is fundamental to starting a business because it stimulates motivation, improves intellectual activity, and provides meaning for daily work. This research investigates the role of entrepreneurial passion as a prelude to entrepreneurial intention. The theory of planned behavior was used as an underpinning theory. A conceptual framework was developed and tested to determine their contributions to entrepreneurial intentions. The correlation between entrepreneurial passion and entrepreneurial intentions is moderated by perception of university support to determine if it enhances the entrepreneurial intention to become a successful entrepreneur. The sample (N = 395) was identified using a convenience sampling technique and is comprised of university business students in the province of Punjab, Pakistan. The questionnaire comprised two sections used for data collection, and Smart-PLS was used to analyze the hypotheses. The findings have indicated that there is a strong positive relationship between entrepreneurial passion and entrepreneurial intentions. The analysis showed that the concept of university support alleviates the relationship between entrepreneurial passion and entrepreneurial intention. The moderation effect of perception of university support on the association between entrepreneurial passion and entrepreneurial intention was recognized in this study. Thus, it called for exploring this moderating effect from other perspectives. As an implication to policy, the government bodies should ensure students have access to an entrepreneurial atmosphere. Specifically, the ministry of education and HEC Pakistan could consider this for the design of university syllabuses, thereby leading to more impactful education of entrepreneurship.
Keywords: 350; entrepreneurial intention; entrepreneurial passion; perception of university support; theory of planned behavior